2012
DOI: 10.1111/j.1365-2265.2011.04302.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistent findings of renal glomerular disease with Hashimoto’s thyroiditis

Abstract: Glomerular pathologies associated with HT are similar to those in the general population, the most common lesions being MGN, FSGS and IgA nephritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…Shima et al (99) revealed in the kidney biopsy of a child with membranous GN and Graves' disease thyroid peroxidase deposits, indicating that not only immune complexes of thyroglobulin but also immune complexes of thyroid peroxidase can cause membranous GN. Notably, the association of thyroid antibody levels with the degree of renal decline in immune-mediated GN has not been yet elucidated (92). It could be speculated that immune-mediated GN and autoimmune thyroidits share common pathways of autoimmunity activation.…”
Section: Glomerular Diseases and Thyroid Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Shima et al (99) revealed in the kidney biopsy of a child with membranous GN and Graves' disease thyroid peroxidase deposits, indicating that not only immune complexes of thyroglobulin but also immune complexes of thyroid peroxidase can cause membranous GN. Notably, the association of thyroid antibody levels with the degree of renal decline in immune-mediated GN has not been yet elucidated (92). It could be speculated that immune-mediated GN and autoimmune thyroidits share common pathways of autoimmunity activation.…”
Section: Glomerular Diseases and Thyroid Disordersmentioning
confidence: 99%
“…Thyroid disorders (both hyper and hypothyroidism) (87)(88)(89) and most commonly auto-immune thyroiditis are associated with glomerulonephritis (GN), including membranous nephropathy (88,90,91), focal segmental glomerulosclerosis (92), minimal change (89, 92), membranoproliferative GN (93) IgA nephropathy (94), and amyloidosis (92). Interestingly, anti-neutrophil cytoplasmic antibody (ANCA) positive crescentic GN has been reported after treatment with propylthiouracil for hyperthyroidism and membranous nephropathy after 131 I administration (95,96).…”
Section: Glomerular Diseases and Thyroid Disordersmentioning
confidence: 99%
“…Another valid clinical question emanating from this case is why a thyroid ultrasonographic examination was performed on a young man with hematuria? Kocak et al [9] has shown a significant association between renal glomerular disease and autoimmune thyroid disease, thus the ultrasonographic examination in this patient referred with microscopical hematuria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that the lesion most commonly associated is Membranous Glomerulonephritis (MGN) followed by Focal Segmental Glomerulosclerosis (FSGS) and Minimal Change Disease (MCD). 2 Several mechanisms have been proposed to explain these associations. Features suggesting a common autoimmune disorder are immune-complex deposition 3 in the glomerular and thyroid basement membrane and association with other autoimmune diseases like type 1 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Autoimmune thyroiditis resulting in hypothyroidism (Hashimoto's) can rarely be associated with concomitant autoimmune glomerular involvement resulting in the development of Nephrotic syndrome. 2 The development of overt proteinuria results in loss of thyroid hormones bound to its carrier proteins. 5 This results in hypothyroidism in a patient with a compromised thyroid gland.…”
Section: Introductionmentioning
confidence: 99%